Discrete Optimization in Architecture Architectural & Urban Layout - Zawidzki, Machi; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2016)
This book presents three projects that demonstrate the fundamental problems of architectural design and urban composition - the layout design, evaluation and optimization. Part I describes the functional layout design of a residential building, and an evaluation of the quality of a town square (plaza). The algorithm for the functional layout design is based on backtracking using a constraint satisfaction approach combined with coarse grid discretization. The algorithm for the town square evaluation is based on geometrical properties derived directly from its plan. Part II introduces a crowd-simulation application for the analysis of escape routes on floor plans, and optimization of a floor plan for smooth crowd flow. The algorithms presented employ agent-based modeling and cellular automata.
Keywords: Buildings -- Design and construction; Computer-aided engineering; Mechanics, Applied; Solids; Human geography; Building materials; Building Construction and Design; Computer-Aided Engineering (CAD, CAE) and Design; Solid Mechanics; Human Geography; Structural Materials